2016
DOI: 10.1016/j.bmc.2016.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of dual 5-HT1A and 5-HT7 receptor ligands

Abstract: 5-HT1A and 5-HT7 receptors have been at the center of discussions recently due in part to their major role in the etiology of major central nervous system diseases such as depression, sleep disorders, and schizophrenia. As part of our search to identify dual targeting ligands for these receptors, we have carried out a systematic modification of a selective 5HT7 receptor ligand culminating in the identification of several dual 5-HT1A and 5-HT7 receptor ligands. Compound 16, a butyrophenone derivative of tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Ligand 1 was bound into all receptors with comparable potency (PIE was − 180.0, − 169 and − 188 kcal/mol, respectively), although experimental studies showed strong activity at 5-HT 1A receptor and moderate with respect to the remaining ones. Since 1 acts as a 5-HT 1A and 5-HT 2A agonist, and 5HT 7 receptor antagonist (such as aripiprazole [45,58]), Fig. 4 analysis allowed to hypothesize about its molecular mechanism of activation/deactivation of receptors.…”
Section: Comparison Of Fmo Results With Previous Work For 5-ht 1a Rementioning
confidence: 99%
“…Ligand 1 was bound into all receptors with comparable potency (PIE was − 180.0, − 169 and − 188 kcal/mol, respectively), although experimental studies showed strong activity at 5-HT 1A receptor and moderate with respect to the remaining ones. Since 1 acts as a 5-HT 1A and 5-HT 2A agonist, and 5HT 7 receptor antagonist (such as aripiprazole [45,58]), Fig. 4 analysis allowed to hypothesize about its molecular mechanism of activation/deactivation of receptors.…”
Section: Comparison Of Fmo Results With Previous Work For 5-ht 1a Rementioning
confidence: 99%
“…19 Inspired by the promising binding affinity profiles of these butyrophenones at the relevant CNS receptors ( Table 3 ), we embarked on an exploration to further understand the SAFIR of these compounds. To begin with, we sought to understand the role of the position of the nitrogen in segment C. The THIQ moiety in 3b was replaced with tetrahydroquinoline and 2,3,4,5-tetrahydro-1H-benzo[ b ]azepine to produce compounds 3c and 3d respectively, resulting in the formation of aromatic nitrogen atoms in both analogs.…”
Section: Resultsmentioning
confidence: 99%
“… MTA = Missed 50% of threshold inhibition, ND = Not determined. * Ki values without the associated SEM, are within 20% of the mean value. ** Binding affinity data from reference 19. a Binding affinity data from reference 28. b Binding affinity data from reference 29; c Binding affinity data from reference 30 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 was previously synthesized and reported by us [14]. The synthetic methods leading to alkylating agents 14, 15, 16 and 17 were also previously reported [14], [15], [16]. Compounds 4 -8 were synthesized as described in Scheme 1a.…”
Section: Chemistrymentioning
confidence: 99%